2008
DOI: 10.13109/zptm.2008.54.4.409
|View full text |Cite
|
Sign up to set email alerts
|

Entwicklung des Fragebogens »ICD-10-Symptom-Rating« (ISR)

Abstract: In a first cross-validation with 108 patients, some rather high correlations were found between the SCL-90-R and the ISR. They ranged from r = 0.78 to 0.37 for the individual syndrome scales, and amounted to r = 0.78 for the GSI versus the total score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
25

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 1 publication
0
75
0
25
Order By: Relevance
“…In einer multiplen Regression wurden Zusammenhänge zwischen diesen mit 0, 1 und 2 codierten Inanspruchnahmegruppen und strukturellen Beeinträchtigungen (OPD-SFK) berechnet. Neben dem OPD-SFK wurde routinemäßig die Summenskala des ICD-10-Symptom-Rating (ISR; Tritt et al 2008) …”
Section: Datenanalyseunclassified
“…In einer multiplen Regression wurden Zusammenhänge zwischen diesen mit 0, 1 und 2 codierten Inanspruchnahmegruppen und strukturellen Beeinträchtigungen (OPD-SFK) berechnet. Neben dem OPD-SFK wurde routinemäßig die Summenskala des ICD-10-Symptom-Rating (ISR; Tritt et al 2008) …”
Section: Datenanalyseunclassified
“…Therefore, this preliminary study showed that the ICD-10-derived symptom scale seems appropriate to be investigated in a thorough validation trial. Manual for Mental Disorders DSM-III-R [17] or the Symptom Checklist SCL-90 [7].…”
Section: Discussionmentioning
confidence: 99%
“…Even in research the screening for depression with valid instruments has demonstrated only limited benefit [5]. In daily practice one might doubt if a lack of knowledge or availability of numerous valid instruments [6][7][8][9][10][11], widely known among specialists, is the problem or rather the lack of time needed for the correct administration of instruments in the face of limited resources. Yet, one would have to admit that even among psychiatrists the discussion which questionnaire should be used remains lively discussed [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ‘ICD-10 Symptom Rating' (ISR) questionnaire was used to assess psychosomatic symptoms such as depression, anxiety disorders, etc. [22]. Participants with severe symptom loads were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%